(untitled) (Global Journal of Human-Social Science, 2012)
This research paper undertakes the examination of the different diagrammatic models of the masscommunications Communication is a natural instinct of all living creatures It is a basic need of all human beings It plays all the more significant role in the present day masscommunication which is complex dynamic and socially oriented Effective models of masscommunication keep the mass-media vibrant vital and smooth sailing First of all we would discuss Mass Communication Mass communication is the academic study of how individuals and entities relay information through mass media to large segments of the population at the same time It is usually understood to relate to newspaper and magazine publishing radio television and film as these are used both for disseminating news and for advertising Sources of Mass Communication are the most important means of framing public opinion and media contents are in accordance of public opinion